Perbedaan Model Pembelajaran Discovery Terbimbing dan Discovery Terpimpin Terhadap Hasil Belajar Kognitif - Septian, Albertus Ivan; Lisnani, L (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2023)
The guided discovery and guided discovery learning models make students more active and discover things during class learning. This research aims to find out how the guided discovery learning model and the guided discovery model differ on cognitive mathematics learning outcomes. This type of research is quantitative research using experimental methods. The sample in this study was the VA and VB classes at SD Xaverius 4 Palembang totaling 54 people through simple random sampling. Data collection techniques used in research are interviews, tests and documentation. The data analysis techniques used are validity test, reliability test, data normality test, homogeneity test, and independent sample t-test. The results of the research show that there are differences in cognitive learning outcomes using the guided discovery learning model and the guided discovery model on the cognitive mathematics learning outcomes of class V students at SD Xaverius 4 Palembang. The results of this research can be used in the world of education in terms of the use of learning models during the mathematics learning process